Compact dual-band bandpass filter using asymmetric stepped impedance stub loaded multimode resonator. Issue 1 (2nd July 2015) - Pal, Manimala; Ghatak, Rowdra; Sarkar, Pankaj
Abstract : This paper presents, a dual-band bandpass filter using asymmetric stepped impedance stub loaded open loop resonator (OLR) for WLAN and WiMAX application. The outer OLR is realized to operate at lower passband of 2.45 GHz which is directly coupled to input and output ports whereas the asymmetric stepped impedance stub that loads the outer resonator contributes to 3.5 GHz passband. The introduction of asymmetric stepped impedance stub provides further control of improving the upper passband edge selectivity of second passband and in shifting the spurious modes away from second band thereby contributing to the wide upper stopband. The insertion loss is within 1.5 dB for each passband with 10 dB passband bandwidth of 250 MHz at both bands. A stopband up to 10 GHz is also obtained. A prototype is developed and the s-parameters obtained from electromagnetic simulation, equivalent transmission line model and measurement are in close agreement. The overall dimension of the filter is 25.45 × 15.89 mm 2 which renders it a compact size.